Achieving sustainability development goals of quality education through “VIDGRATION” method - Siti Hawa Harith; Norsharina Zabidi; Syazwan Syah Zulkifly; Nur’Jila Mohammad (Discover Sustainability)
Abstract Flexible teaching by applying the “VIDGRATION” method, a video-based teaching tool used explicitly for non-law students, is one of the efforts to support the Sustainable Development Goal (SDG) 4 of Quality Education. This study investigates the effectiveness of the “VIDGRATION” method in improving non-law students’ understanding of a law-related subject. Non-law students mostly face difficulty with law-related subjects due to their unfamiliarity with law terms and wording. Therefore, these students cannot understand the lesson and score poorly during examinations. The “VIDGRATION” method is being introduced to facilitate the non-law students’ learning process. This qualitative study was undertaken toward 99 non-law students who enrolled on the Human Resource Management subject. This intervention study was conducted in three stages: problem identification, intervention and evaluation. All data were triangulated from the instructor’s and students’ reflections, focus group interviews, and comparisons between the pre-and post-quiz results. The results show that the “VIDGRATION” method has successfully improved the non-law students’ understanding of law-related subjects. In addition, the non-law students also enhance their cognitive skill, time management skills, readiness to study and develop critical thinking skills when applying real working scenarios.